Application of the Principles of Accounting Ethics in Java culture - Muhammad Aras Prabowo; Rismawati; Vita Aulia; Mariska Nur Hanifah (Innovation Business Management and Accounting Journal, 2025)
This research examines the application of ethical accounting principles in Javanese culture as well as the noble values of Javanese culture that can support the application of accounting ethics with a focus on Indonesian society. This approach is carried out through a literature review that studies the relationship between Javanese cultural values and the accountant's code of ethics. Accounting ethical theory, Javanese culture, and the Indonesian Accounting Code of Ethics (KEAI) are the focus of this research. The results of the literature review show that Javanese culture has noble values such as bener (honesty), ngrasa (openness), responsibility (responsibility), gotong royong (gotong royong), isin/sungkan (shame), deliberation (deliberation), tepo seliro (mutual respect), rahayu (hope for goodness), ojo angkuh (don't be arrogant), and mergawe seng temenan (work hard). consistent with ethical accounting principles of integrity, objectivity, and accountability. The application of Javanese cultural values in accounting practices can help ensure that accountants carry out their duties with integrity, honesty, and high responsibility while still paying attention to the interests of society.